Improving enteral nutrition delivery in the critically ill trauma and surgical population. Issue 5 (15th March 2022) - McCartt, Jason; Loszko, Abigail; Backes, Kehaulani; Cunningham, Kyle; Evans, Susan; Draughon, Matthew; Sachdev, Gaurav
Abstract: Background: Critically ill trauma and surgical patients often fail to achieve adequate enteral nutrition (EN) support. We hypothesize that implementation of an evidence‐based, multidisciplinary nutrition enhancement protocol (EP) will improve delivery of EN in critically ill trauma and surgical patients and align our institution with nationally recommended guidelines. Methods: The study compared patients prior to protocol (PP) with patients after implementation of the EP. The primary outcome was delivery of >80% of daily prescribed EN kilocalories in critically ill trauma and surgical patients during their intensive care unit stay. Data were prospectively captured from daily rounds and the electronic health record. Statistical analysis was conducted to compare data between groups using Student t test for continuous variables and chi‐square test for categorical variables. Results: In total, 256 patients in the PP group (2663 EN days) were compared with 232 patients in the EP group (2059 EN days). The primary outcome of average percentage of nutrition delivered (based on 24‐h kilocalorie requirements) improved after the implementation of the EP (75.3% PP vs 85.5% EP; P  < 0.01). This improvement was evident in surgical (69.9% PP vs 78.7% EP; P  < 0.01) and trauma (78.2% PP vs 87.3% EP; P  < 0.01) subpopulations. The secondary outcome of percentage of patients receiving >80% of nutrition goal also improved (52.7% PP vs 65.2% EP; P  < 0.01). Conclusion: Implementation of an EP significantly increased delivery of EN by 10.2% and achieved compliance with American Society for Parenteral and Enteral Nutrition and Society of Critical Care Medicine recommended guidelines for critically ill trauma and surgical patients.